The effects of schooling on rural unemployment in Ethiopia - Abdisa Olkeba; Tsegamariam Dula Sherka; Paulos Gutema; Degefa Tolossa Degaga; Abate Mekuriaw Bizuneh; Alemu Azmeraw Bekele (Cogent Economics & Finance, 2023)
Nowadays, education is considered an instrument that we use to eradicate poverty. It is also presumed as an indicator of modernization and a development realization tool. Education creates an opportunity to be employed in good positions in reducing unemployment. Scholars debate whether education reduces rural unemployment. Some scholars argue that education is a powerful weapon to reduce rural unemployment. Others encounter that education does not necessarily decrease rural unemployment. This paper describes the effects of schooling on rural unemployment in Ethiopia. We used a quantitative approach with a descriptive research design in this study. A sample of 8700 participants, based on the Ethiopian Central Statistics Agency data collected in 2021, was obtained. We used descriptive and probit models to analyze the data. The descriptive results showed that rural unemployment is unequally distributed based on education, sex, and regional states. The majority are still participating in the agriculture sector. Besides, the finding also reveals that lack of job opportunities, training, experience, and unrelated jobs to education in rural areas is the cause of unemployment. However, the probit model result shows that schooling has a statistically significant positive effect on employment. As a result, for a one-unit increase in education, the probability of employment increases by 0.15. It concludes that schooling is paramount in decreasing rural unemployment in Ethiopia if much attention is given. We recommend that the government should transform rural areas' activities from agricultural-oriented to services-oriented activities to create extensive job opportunities in rural areas for rural youths, especially educators.
Keywords: 330; effects; Ethiopia; probit model; rural; schooling; unemployment